Genetic variants of vitamin D metabolism-related DHCR7/NADSYN1 locus and CYP2R1 gene are associated with clinical features of Parkinson's disease. (4th May 2022) - Alaylıoğlu, Merve; Dursun, Erdinç; Genç, Gençer; Şengül, Büşra; Bilgiç, Başar; Gündüz, Ayşegül; Apaydın, Hülya; Kızıltan, Güneş; Gürvit, Hakan; Hanağası, Haşmet; Öztop Çakmak, Özgür; Ertan, Sibel; et al.
Abstract: Purpose/aim of the study: Parkinson's disease (PD) is the second most common neurodegenerative disorder. Vitamin D deficiency is suggested to be related to PD. A genome-wide association study indicated that genes involved in vitamin D metabolism affect vitamin D levels. Among these genes, single nucleotide polymorphisms (SNPs) of the vitamin D receptor ( VDR ) and vitamin D binding protein ( VDBP/GC ) genes have also been demonstrated to be associated with PD risk. Our aim was to investigate the relevance of SNPs within the 7-dehydrocholesterol reductase/nicotinamide adenine dinucleotide synthetase 1 ( DHCR7/NADSYN1 ) locus and vitamin D 25-hydroxylase ( CYP2R1 ) gene, which encode important enzymes that play a role in the vitamin D synthesis pathway, with PD and its clinical features. Materials and methods: Genotypes of 382 PD patients and 240 cognitively healthy individuals were evaluated by a LightSNiP assay for a total of 10 SNPs within the DHCR7/NADSYN1 locus and CYP2R1 gene. Results: There were no significant differences in the allele and genotype distributions of any of the SNPs between any patient groups and healthy subjects. However, our results indicated that all of the SNPs within the DHCR7/NADSYN1 locus and CYP2R1 gene, except rs1993116, were associated with clinical motor features of PD including initial predominant symptom, freezing of gait (FoG) and falls as well as disease stage and duration of the disease. Conclusions: In conclusion, genetic variants of the DHCR7/NADSYN1 locus and the CYP2R1 gene might be related to the inefficient utilization of vitamin D independent from vitamin D levels, and it might result in differences in the clinical features of PD patients.